The Prevalence and Incidence of Dementia with Lewy Bodies: a Systematic Review. (April 2016) - Hogan, David B.; Fiest, Kirsten M.; Roberts, Jodie I.; Maxwell, Colleen J.; Dykeman, Jonathan; Pringsheim, Tamara; Steeves, Thomas; Smith, Eric E.; Pearson, Dawn; Jetté, Nathalie
ABSTRACT: Background: Population-based prevalence and incidence studies are essential for understanding the societal burden of dementia with Lewy bodies (DLB). Methods: The MEDLINE and EMBASE databases were searched to identify publications addressing the incidence and/or prevalence of DLB. References of included articles and prior systematic reviews were searched for additional studies. Two reviewers screened all abstracts and full-text reviews, abstracted data and performed quality assessments. Results: Twenty-two studies were included. Incidence rates ranged from 0.5 to 1.6 per 1000 person-years. DLB accounted for 3.2-7.1% of all dementia cases in the incidence studies. Point and period prevalence estimates ranged from 0.02 to 63.5 per 1000 persons. Increasing prevalence estimates were reported with increasing age. DLB accounted for from 0.3 to 24.4% of all cases of dementia in the prevalence studies. Conclusions: DLB becomes more common with increasing age and accounts for about 5% of all dementia cases in older populations. RÉSUMÉ: Prévalence et incidence de la démence à corps de Lewy : revue systématique du sujet. Contexte: Les études de population sur sa prévalence et son incidence sont essentielles à la compréhension du fardeau social de la démence à corps de Lewy (DCL). Méthodologie: Nous avons identifié les publications sur l'incidence et/ou la prévalence de la DCL dans les bases de données MEDLINE et EMBASE. Nous avons recherché des études supplémentaires dans les articles et les revues systématiques antérieures cités à titre de références. Deux évaluateurs ont examiné tous les résumés et les évaluations de textes intégraux et l'extraction des données, et ils ont évalué la qualité des publications. Résultats: Vingt-deux études ont été incluses. Les taux d'incidence allaient de 0, 5 à 1, 6 par 1 000 personnes-années. La DCL constituait 3, 2 à 7, 1% de tous les cas de démence dans les études sur l'incidence. Les estimés de prévalence ponctuelle et par période allaient de 0, 02 à 63, 5 par 1 000 personnes. Des taux croissants de prévalence étaient rapportés en association avec l'augmentation de l'âge des sujets. La DCL était responsable de 0, 3 à 24, 4% de tous les cas de démence dans les études de prévalence. Conclusions: La DCL est plus fréquente avec l'âge et constitue environ 5% de tous les cas de démence dans les populations plus âgées.